The Discriminative Power of Different Olfactory Domains in Parkinson's Disease - Zhao, Yuwen; He, Yan; He, Runcheng; Zhou, Yangjie; Pan, Hongxu; Zhou, Xiaoting; Zhu, Liping; Zhou, Xun; Liu, Zhenhua; Xu, Qian; Sun, Qiying; Tan, Jieqiong; et al. (Frontiers in Neurology, 2020)
Background and purpose Olfactory dysfunction is one of the most common non-motor symptoms in Parkinson’s disease (PD) preceding the motor symptoms for years. This study aimed to evaluate different olfactory domains in PD patients in comparison with healthy controls, and to explore the relationships among olfactory deficit and other clinical manifestations in patients with PD. Methods Sniffin’ Sticks test, which detects olfactory threshold, discrimination, and identification (TDI), were conducted in 500 PD patients and 115 controls. Furthermore, demographic and clinical data including motor and other non-motor symptoms were collected. Results In the single olfactory model, the identification test showed the area under the ROC curve (AUC = 0.818), followed by threshold test (AUC = 0.731) and discrimination test (AUC = 0.723). Specifically, the identification test has a similar discriminative power as the TDI score (0.818 and 0.828 respectively, p = 0.481). In the integrated olfactory model involved with other non-motor manifestations, identification test scores performed as good as the TDI score in differentiating PD patients from controls (0.916 and 0.918 respectively, p = 0.797). In PD patients, age and cognition together explained 7.5% of the variance of the threshold score, while age, cognition, and gender accounted for the 15.2% explained variance of the discrimination score, while cognition, age, the ability of daily living and gender together interpreted 11.1% of the variance of the identification score. Conclusion Our results indicated the identification domain was the most practical olfactory factor in differentiating PD patients, and the combination of several different manifestations was better than a single symptom. Furthermore, the olfactory identification score may be associated with the ability of daily living.